Предмет: Алгебра,
автор: dashapoliat
Решите уравнение:
3-(x-3)(x+2)+4(2-x)=7(x+1)-(x-1)
Ответы
Автор ответа:
0
3 - x² - 2x + 3x + 6 + 8 - 4x = 7x + 7 - x + 1
3 - x² - 2x + 3x + 6 + 8 - 4x - 7x - 7 + x - 1 = 0
-x² - 10x + 9 = 0
D = 100 - 4 * (-1) * 9 = 64
x1,2 = 10 ± 8/ -2
x1 = -9
x2 = -1
3 - x² - 2x + 3x + 6 + 8 - 4x - 7x - 7 + x - 1 = 0
-x² - 10x + 9 = 0
D = 100 - 4 * (-1) * 9 = 64
x1,2 = 10 ± 8/ -2
x1 = -9
x2 = -1
Похожие вопросы
Предмет: Литература,
автор: tupolnikandriana
Предмет: Алгебра,
автор: serayadora
Предмет: Литература,
автор: Proroekskskk
Предмет: История,
автор: Эрика0125
Предмет: Литература,
автор: svetik7cvetik2503